Proteomic analysis of colony morphology variants of Burkholderia pseudomallei defines a role for the arginine deiminase system in bacterial survival. - Chantratita, N; Tandhavanant, S; Wikraiphat, C; Trunck, L; Rholl, D; Thanwisai, A; Saiprom, N; Limmathurotsakul, D; Korbsrisate, S; Day, N; Schweizer, H; Peacock, S (2012)
Colony morphology variation of Burkholderia pseudomallei is a notable feature of a proportion of primary clinical cultures from patients with melioidosis. Here, we examined the hypothesis that colony morphology switching results in phenotypic changes associated with enhanced survival under adverse conditions. We generated isogenic colony morphology types II and III from B. pseudomallei strain 153 type I, and compared their protein expression profiles using 2D gel electrophoresis. Numerous proteins were differentially expressed, the most prominent of which were flagellin, arginine deiminase (AD) and carbamate kinase (CK), which were over-expressed in isogenic types II and III compared with parental type I. AD and CK (encoded by arcA and arcC) are components of the arginine deiminase system (ADS) which facilitates acid tolerance. Reverse transcriptase PCR of arcA and arcC mRNA expression confirmed the proteomic results. Transcripts of parental type I strain 153 arcA and arcC were increased in the presence of arginine, in a low oxygen concentration and in acid. Comparison of wild type with arcA and arcC defective mutants demonstrated that the B. pseudomallei ADS was associated with survival in acid, but did not appear to play a role in intracellular survival or replication within the mouse macrophage cell line J774A.1. These data provide novel insights into proteomic alterations that occur during the complex process of morphotype switching, and lend support to the idea that this is associated with a fitness advantage in vivo.